2006
DOI: 10.5860/crl.67.5.418
|View full text |Cite
|
Sign up to set email alerts
|

Plagiarism Instruction Online: Assessing Undergraduate Students’ Ability to Avoid Plagiarism

Abstract: This study assesses undergraduate students' understanding of plagiarism through the use of an interactive, Web-based tutorial, Plagiarism: The Crime of Intellectual Kidnapping. The author details the instructional design process used to create this information literacy resource and integrate it into the curriculum. Data from 2,829 student quiz scores are analyzed to assess student learning. The results of this study indicate that students have difficulty grasping concepts related to paraphrasing. A comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 12 publications
3
53
0
2
Order By: Relevance
“…They especially need more opportunities to practice paraphrasing, in order to develop a better understanding of the concept and be able to apply it in their own texts. This result is supported by a larger study carried out at San José State University (Jackson, 2006). It shows that such difficulties could be a cause of possible misuse of information sources.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…They especially need more opportunities to practice paraphrasing, in order to develop a better understanding of the concept and be able to apply it in their own texts. This result is supported by a larger study carried out at San José State University (Jackson, 2006). It shows that such difficulties could be a cause of possible misuse of information sources.…”
Section: Discussionsupporting
confidence: 73%
“…A study carried out at San José State University (Jackson, 2006) showed that students lacked the ability to apply the concept of paraphrasing in practice; they consequently need more opportunities to practice paraphrasing in order to develop a better understanding of the concept and to be able to apply it in their own texts. In her literature review, Jackson points to previous research which shows that students do not understand the concept of plagiarism and lack the knowledge and skills to avoid it.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study indicated that the students had "difficulty grasping concepts related to paraphrasing." 4 Also, the post-test results showed a 6 percent improvement in student scores over the pre-test results. Karl Woodworth and Linda Markwell report in a 2005 article on the results of an Ovid MEDLINE pre-test given to incoming residents at Emory University's School of Medicine.…”
Section: Literature Reviewmentioning
confidence: 92%
“…A study accomplished at the San José State University by Jackson [24] presented that the students had inability to apply the concept of paraphrasing in practice; they consequently need extra chances for training to practice paraphrasing to be able to apply it in their texts. In addition, these results were supported by Idiegbeyanose et al [25] results who found a significant positive relationship at r = 0.294 and p < .05, between knowledge and practice that implies when awareness increases, practices will also improve.…”
Section: Discussionmentioning
confidence: 99%